(untitled) (Asian Journal of Social Science Studies, 2022)
Straw weaving is a traditional handicraft in China, which is characterized by the use of local herbs as raw materials, after artistic processing, to make beautiful and practical handicrafts, such as straw hats, straw mats and so on. This kind of craft has a long history and a wide range of distribution. It is very popular in Hebei, Shandong, Zhejiang and other places in China. Among them, Hebei Daming grass-knitting is listed in the second batch of national intangible cultural heritage list in 2008, and other local straw weaving crafts are also listed as provincial and municipal intangible cultural heritage in succession. Since the report of the 19th National Congress of the Communist Party of China in 2017 put forward the strategy of rural revitalization for the first time, the CPC Central Committee has always attached great importance to rural revitalization. In 2021, the Law of the People’s Republic of China on the Promotion of Rural Revitalization was adopted to provide legal guarantee for the work of rural revitalization and clearly put forward measures to protect agricultural cultural heritage and intangible cultural heritage. Combining straw weaving technology with rural revitalization and developing straw weaving industry in rural areas can not only promote the inheritance and development of intangible cultural heritage, but also produce economic benefits and drive rural revitalization. However, in the process of combining the two, there are many problems.